2019
DOI: 10.1186/s13031-019-0186-0
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to protect and maintain health care services in armed conflict – meeting SDGs 3 and 16

Abstract: The escalation of conflict in the Middle East coincides with an emerging trend of attacks on healthcare. Protection of health personnel, health services and humanitarian workers is no longer respected. This compromises the achievement of the United Nations Sustainable Development Goals 3 – towards health for all, and 16 – towards justice and peace. The Centre for Global Health at the University of Oslo, the Peace Research Institute Oslo and the Norwegian Red Cross co-organised a meeting exploring how conflict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 3 publications
(4 reference statements)
0
30
0
Order By: Relevance
“…Medical professionals may not be punished for treating those in need of help (ICRC , 1977. Despite legal protections, health care has been targeted in many armed conflicts (Briody et al 2018;Druce et al 2019;Rubenstein and Bittle 2010;Footer et al 2014;Lafta and Falah 2019;The Safeguarding Health in Conflict Coalition 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Medical professionals may not be punished for treating those in need of help (ICRC , 1977. Despite legal protections, health care has been targeted in many armed conflicts (Briody et al 2018;Druce et al 2019;Rubenstein and Bittle 2010;Footer et al 2014;Lafta and Falah 2019;The Safeguarding Health in Conflict Coalition 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also revealed the negative impact of conflict on access to health services. As a result of violence, targeted attacks on infrastructure and providers, displacement, security concerns, and resource shortages citizens are unable to access the care they need 1,8–10 . Furthermore, prolonged violence within these contexts often becomes normalized resulting in increased gender‐based violence, sexual assault, and prostitution.…”
Section: Introductionmentioning
confidence: 99%
“…As a FCAS, the healthcare system in Burundi is likely to have a decreased capacity for equitable health care delivery with the healthcare system that exists being fragmented and containing silos rather than continuums of care 1,5 . Barriers to accessing health facilities also increase with security concerns for both users and practitioners as pregnant women may feel that it is unsafe to travel to healthcare facilities and healthcare workers are at risk of attack 1,8 . The result of conflict in this context is a shortage of healthcare workers who are able to provide ANC and assistance during childbirth to women.…”
Section: Introductionmentioning
confidence: 99%
“…Asides from general physical and mental health consequences, con icts worsen health provision, and complicate health services operations and processes (6). These effects are a consequence of direct damages to health facilities and health care infrastructures, con ict-related threats to health professionals, or structural problems such as inadequate institutions for promoting people's rights and opportunities (7). Health services may be forced to stop or to operate under challenging circumstances, which, in the long run, may lead health services to be unstable or rugged to maintain operations overtime (8).…”
Section: Introductionmentioning
confidence: 99%